2021
DOI: 10.2147/dmso.s314709
|View full text |Cite
|
Sign up to set email alerts
|

FOXA1 Suppresses SATB1 Transcription and Inactivates the Wnt/β-Catenin Pathway to Alleviate Diabetic Nephropathy in a Mouse Model

Abstract: Objective Diabetic nephropathy (DN) represents the most common diabetic complication that may lead to end-stage renal disease. This work focused on the effect of FOXA1 on the DN development and the molecular mechanism. Methods A mouse model of DN was induced by high-fat diets and streptozotocin. The concentrations of blood glucose and urinary protein in mice, and the pathological changes in mouse kidney tissues were determined. A podocyte cell line MPC-5 was treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Moreover, preventing MAPK activation, which inhibits inflammation and apoptosis, can ameliorate renal fibrosis (52). Furthermore, inactivation of the WNT/β-catenin signaling pathway can inhibit podocyte apoptosis and DN progression (53). Overall, these findings are consistent with our data mining results.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, preventing MAPK activation, which inhibits inflammation and apoptosis, can ameliorate renal fibrosis (52). Furthermore, inactivation of the WNT/β-catenin signaling pathway can inhibit podocyte apoptosis and DN progression (53). Overall, these findings are consistent with our data mining results.…”
Section: Discussionsupporting
confidence: 88%
“…FOXA1 has been reported to restrain SATB1 transcription and inactivate the Wnt/β‐Catenin pathway to mitigate diabetic nephropathy in a mouse model (Zhu et al, 2021). The Wnt/β‐Catenin pathway has been clarified to be elevated in cancer and takes a major role in proliferation, invasion, apoptosis, and angiogenesis (Vallée et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the link between FOXA1 and NEDD4, it was elevated FOXA1 in FARAGE cells with enhancive NEDD4 and detected an elevation in FOXA1 (Figure 5a). Subsequent FOXA1 has been reported to restrain SATB1 transcription and inactivate the Wnt/β-Catenin pathway to mitigate diabetic nephropathy in a mouse model (Zhu et al, 2021). The Wnt/β-Catenin pathway has been clarified to be elevated in cancer and takes a major role in proliferation, invasion, apoptosis, and angiogenesis (Vallée et al, 2021).…”
Section: Foxa1 Counteracts Nedd4's Function In Dlbclmentioning
confidence: 99%
“…On the other hand, Vatamaniuk et al [96] demonstrated that Foxa1-deficient mice exhibited impaired insulin secretion due to uncoupled oxidative phosphorylation. Zhu et al [97] showed that FOXA1 suppressed the transcription of special AT-rich sequence binding protein 1 and inactivated the Wnt/β-catenin pathway to alleviate diabetic nephropathy in a mouse model. However, the role of FOXA1 in the relationship between diabetes and breast cancer remains to be determined in future studies.…”
Section: Foxa1 In Breast Cancermentioning
confidence: 99%